Social touch deprivation during the COVID-19 pandemic and reduced well-being - Gerdes, Antje B. M.; Roether, Svenja Mareike; Alpers, Georg W. (Frontiers in Psychology, 2026)
IntroductionSocial distancing was mandatory during the COVID-19 pandemic to curtail the spread of infections. This hampered interactions with people who did not share households, including the exchange of social touch. We explored how social distancing influenced people’s experience of social touch and its impact on psychological well-being during the pandemic.MethodsIn an online survey carried out in Germany (N = 287; 77.5% female), we assessed the estimated number of episodes per day involving social touch in different contexts (personal and professional surroundings) as well as individual factors that may influence the frequency of social touch (e.g., relationship status, living arrangement). Participants retrospectively compared episodes for the time before the outbreak versus during mandatory social distancing. In addition, we examined whether social touch predicts psychological well-being and sought to identify protective factors.ResultsAs expected, during the pandemic, social touch was less frequent in both personal and professional settings. However, individuals in a relationship reported relatively stable levels of social touch in personal contexts, unlike those without a relationship. Overall well-being declined during the pandemic, but this decline was less pronounced among those who experienced more social touch independently of relationship status.DiscussionSocial distancing in a Western society substantially reduced social touch, which in turn harmed psychological well-being, supporting the notion that touch is a relevant factor for resiliency. This research highlights that individuals who are not in a relationship are particularly vulnerable to the effects of social distancing.